The Self-Identity Construction of Arab Young Women Who Were Abused in Childhood within a Complex Cultural and Socio-Political Context - Alnabilsy, Raghda (Journal of family violence, 2023)
Exposure to violence in childhood and adolescence may lead to negative self-identity construction in young women. These phenomena are exacerbated in the context of Arab young women, who belong to both a national minority in Israel and to a gender subject to exclusion, oppression, and discrimination in society in general and in Arab society in particular. The aim of this qualitative study was to examine how Arab young women abused in childhood construct their self-identity within their gender, cultural, class, and national context. The study was based on 20 semi-structured interviews with Arab young women in Israel, who were victims of violence in childhood (aged 18–26). Construction of self-identity, as described by participants, included: harmed self (self under guilt; lack of confidence in one’s abilities and giving up; insecure self; belittling of self); self divided between loyalty to the family and society and a desire for self-realization; the self versus the other. In addition, some participants, later in young adulthood, were able to change their perception of self and see themselves as capable, strong, and not guilty of the violence directed against them. These women transitioned from absent to present femininity. The study provides a broader definition of self-identity construction among young women abused in childhood, including Arab young women in Israel in their intersecting contexts and the limitations imposed by multiple marginality. This broader understanding enables the design of context-informed therapeutic intervention practices.